The Effect of Workload on Employee Performance with Flexibility in Working Hours as an Intervening Variable at PT. Telkom Indonesia Witel Jambi - Variha, Anetha; Sumarni, Sumarni; Setiawan, Wahyu Juari (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of workload on employee performance with flexibility of working hours as an intervening variable in PT Telkom Indonesia Witel Jambi. The research method used is a quantitative approach with an analysis technique using SMARTPLS version 4.0. The sample in this study consisted of 40 employees selected through a saturated sampling technique. Data collection was carried out through observations, interviews, and questionnaires. The results of the study show that workload has a positive and significant influence on employee performance. The flexibility of working hours also plays a role as a mediating variable that optimizes the influence of workload on performance. These findings emphasize the importance of implementing a balanced workload policy and flexibility in managing working hours to improve employee productivity and well-being.